Blockade of CD47 or SIRPα: a new cancer immunotherapy. (2nd October 2020) - Murata, Yoji; Saito, Yasuyuki; Kotani, Takenori; Matozaki, Takashi
ABSTRACT: The CD47-Signal regulatory protein α (SIRPα) singling axis acts as a crucial regulator that limits the phagocytic activity of professional phagocytes such as macrophages. Recent studies have demonstrated that the interaction between CD47 on tumor cells and SIRPα on macrophages is implicated in the ability of tumors to evade immunosurveillance. Targeting the CD47-SIRPα interaction is therefore considered to be a promising approach for cancer therapy. Herein, we review some of studies displaying the potential clinical application of antibodies and other modalities that target the CD47-SIRPα interaction. Current limitations of the CD47-SIRPα-targeted immunotherapeutic approaches are also discussed as well as other avenues for future study to improve the current strategies in targeting the CD47-SIRPα signaling axis for cancer immunotherapy.